Proceedings of the 13th International Conference on Damage Assessment of Structures : DAMAS 2019, 9-10 July 2019, Porto, Portugal /: DAMAS 2019, 9-10 July 2019, Porto, Portugal. ([2020]) - Unknown
No abstract available